Greenland, Kejser Franz Joseph Fjord and Nordenskiöld Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
17-20 July 31, 1931. Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. Extreme inner end. Nordenskjold Glacier. Photo taken looking W.N.W. from motor boat. This is No. 3 in pan A.